2008
DOI: 10.1152/ajpendo.90371.2008
|View full text |Cite
|
Sign up to set email alerts
|

12-Lipoxygenase-knockout mice are resistant to inflammatory effects of obesity induced by western diet

Abstract: Inflammation is a key pathological process in the progression of atherosclerosis and type 2 diabetes. 12/15-lipoxygenase (12-LO), an enzyme involved in fatty acid metabolism, may contribute to inflammatory damage triggered by stressors such as obesity and insulin resistance. We hypothesized that mice lacking 12-LO are protected against inflammatory-mediated damage associated with a "western" diet. To test this hypothesis, age-matched male 12-LO knockout (12-LOKO) and wild-type C57BL/6 (B6) mice were fed either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 70 publications
8
126
0
Order By: Relevance
“…These results indicate enhanced inflammation in adipocytes and adipose tissue of obese Zucker rats that is associated with increased 12-and 5-LO expression and activity. An earlier study from our laboratory demonstrated that in the high-fat-fed mouse model, global deletion of 12-LO significantly reduces macrophage infiltration and a proinflammatory response in visceral adipose tissue (43). Thus, we propose that 12-LO activation may be a link to adipose tissue inflammation in the insulin-resistant obese Zucker rats.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These results indicate enhanced inflammation in adipocytes and adipose tissue of obese Zucker rats that is associated with increased 12-and 5-LO expression and activity. An earlier study from our laboratory demonstrated that in the high-fat-fed mouse model, global deletion of 12-LO significantly reduces macrophage infiltration and a proinflammatory response in visceral adipose tissue (43). Thus, we propose that 12-LO activation may be a link to adipose tissue inflammation in the insulin-resistant obese Zucker rats.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, 12-LO has recently been linked to inflammation in high-fat diet-induced obesity in mice (43,54). 5-LO and 5-FLAP have also been implicated to play roles in obesity and insulin resistance (18,24,28), and a recent study demonstrated the role of 5-FLAP in adipose tissue inflammation in experimental obesity (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the majority of atherogenic risk factors are associated with increased 12/15-LO expression (5)(6)(7)(8), and disruption of 12/15-LO gene-protected ApoE ÏȘ/ÏȘ mice from developing high-fat diet-induced atherosclerosis (24), we studied the role of 12/15-LO in EC barrier dysfunction. A quiescent monolayer of HUVECs, when treated with 5-, 12-, and 15(S)-HETE, the AA cleavage products of 5-, 12-, and 15-LO, the paracellular permeability of the monolayer, as measured by passive diffusion of FITC-conjugated dextran, significantly increased (Fig.…”
Section: (S)-hete Increases Ec Permeability-loss Of Barrier Func-mentioning
confidence: 99%
“…In the NOD mouse, 12-lipoxygenase deletion confers a near complete protection against type 1 diabetes and also reduces immune cell activation [17,23]. Interestingly, two independent groups have shown that 12-lipoxygenase activation also participates in high-fat-induced insulin resistance and adipose tissue inflammation [24,25]. Deletion of 12-lipoxygenase significantly inhibits the development of insulin resistance in mice fed a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%